Halal food products by urban Malay Muslims / Hasman Abdul Manan - Abdul Manan, Hasman (Institute of Graduate Studies, UiTM, 2018)
The study offered one of the early initiatives in exploring urban Malay Muslim consumers' food-related behaviors toward Halal food products from non-Muslim countries; within a collectivist and urban social setting. The conceptual framework was adopted from the Theory of Planned Behavior and later extended to include three new variables based on empirical evidence in existing literature from several fields of studies. Structural equation modeling and Statistical Package for the Social Sciences were the statistical procedures for a sample of 450 urban Malay Muslims. The results demonstrated the proposed structural model appropriately fits the observed data hence, the results allowed the study to draw its conclusions. Perceived knowledge had successfully predicted trust, subjective norm, and perceived behavioral control; however, it did not show any relationships with attitude and receptiveness. In contrast, perceived knowledge and distrust had a significant positive link instead of the hypothesized negative relationship. Also, the results established receptiveness was the function of subjective norm, perceived behavioral control, trust, and distrust. Nonetheless, the correlations between perceived knowledge-attitude and attitude-receptiveness constructs were not consistent with present theories. Perceived control behavior had demonstrated to be the strongest predictor of urban Malay Muslim consumers' receptiveness toward Halal food products from non-Muslim countries…